Optimized Indoor Propagation Model for Office Environment at GSM Frequencies - (:unkn) unknown (IEEE, 2015)
This work outlines indoor propagation models for frequencies of GSM band. Estimating signal strength is critical for picocell deployment because low signal strength could mean gaps in the coverage while excessively high signal levels may have risks going over electromagnetic exposure rules. Because of this need, it is important to have accurate indoor propagation models. Thus, this study searched accuracy of existing indoor propagation models and derives an efficient and quick method optimized for an office environment. In order to test the existing indoor propagation models, measurements were taken at an office building. Then models arc implemented to each measurement scenario. Predictions of the models are then compared to actual measurement results. Performance of each model is compared with their absolute mean errors.